Severe Eosinophilic Syndrome Associated with the Use of Probiotic Supplements: A New Entity? - Fabian A. Mendoza; Shivani Purohit; Lawrence Kenyon; Sergio A. Jimenez (Case Reports in Rheumatology)
Severe eosinophilic syndromes related to the administration or use of unsuspected immunogenic substances have been described previously. Many of these diseases presented initially as clusters or isolated cases. The spanish toxic oil syndrome, the eosinophilia myalgia syndrome, and nephrogenic systemic fibrosis are examples of such diseases. We describe 2 cases of a severe eosinophilic syndrome characterized by marked peripheral blood eosinophilia (>15,000 cells/ml), mononeuritis multiplex, and necrotizing vasculitis which developed in a close temporal association with the recent onset use of nonprescription probiotics. There was no history of a prior autoimmune disease. Although both cases had prompt response to immunosuppression with rapid resolution of peripheral blood eosinophilia and accompanying constitutional symptoms, they remained with permanent neurological deficits.